PENGARUH TINGKAT KEMISKINAN DAN ANGKA PUTUS SEKOLAH TERHADAP PEKERJA ANAK DI INDONESIA - Roha Datul Aisy; Fanny Nailufar (JURNAL EKONOMIKA INDONESIA, 2022)
This study examined the influence of Poverty Rate and Dropout Rates on Child Labor in Indonesia. This study used secondary data obtained from the publications of the Central Bureau of Statistics of Indonesia for 21 years (1999-2019). To achieve the results of this study, a dynamic VAR model analysis using the Eviews 9 program was used. The results indicated that poverty rate had a positive and significant effect on child labor in Indonesia and the dropout rate did not have a significant effect on child labor in Indonesia. The researcher hopes that the government can increase family economic empowerment, expand educational opportunities for child workers and their families, provide more employment opportunities to reduce poverty